Transcriptional activation function is not required for stimulation of DNA replication by bovine papillomavirus type 1 E2. - Grossel, M J (1996)
Bovine papillomavirus type 1 replication was previously shown to require both the E1 initiator protein and the E2 transactivator protein. We show here that E1, in the absence of E2, is sufficient for low-level bovine papillomavirus type 1 DNA replication in C-33A cells. In addition, studies of genetically isolated E2 point mutants demonstrate that enhancement of replication by E2 does not require its transcriptional activation function. The uncoupling of the E2 functions suggests that stimulation of transcription and replication by enhancer proteins occurs via divergent mechanisms.